Financial sector development and sectoral output growth evidence from South Africa - Tongo, Yanga (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2012)
The goal of the study is to examine the relationship between financial sector development and output growth in the agricultural, mining and manufacturing sectors in South Africa. The analysis is based on the hypothesis that financial development is essential for promoting production growth in an economy. To test the hypothesis, in the South African context, the vector autoregressive model (VAR) framework and Granger causality test are applied to a quarterly data set starting from 1970 quarter one to 2009 quarter four. The results suggest that financial intermediary development (bank based measure) and stock market development (market based measure) have a positive impact on output growth in the agriculture, mining and manufacturing sectors in South Africa. There is evidence of a one way causal relationship between financial sector development and sectoral output growth. Particularly, there is evidence that financial intermediary development and stock market development causes output growth in the agriculture, mining and manufacturing sectors in South Africa. However, there is no evidence showing causality running from sectoral output growth to financial sector development. The results provide evidence supporting the theory which states that financial development is essential to promote output growth in a country i.e. in our case South Africa. Thus an efficient financial system which promotes efficient channeling of resources towards the agricultural, mining and manufacturing sectors should be built.
Keywords: Economic development -- South Africa; Agriculture -- Economic aspects -- South Africa; Mineral industries -- Economic aspects -- South Africa; Manufacturing industries -- Economic aspects -- South Africa; South Africa -- Economic conditions; Autoregression (Statistics); Econometric models; Stock exchanges -- South Africa